Diversity of Sub Order Rhopalocera in Langsa City Forest Park, Aceh - Vira Anggrela; Abdul L. Mawardi; Sri Jayanthi (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Langsa Urban Forest Park is a protected forest area that serves as a natural habitat for various flora and fauna, both wild and cultivated. One of the organisms that can be found there is an insect from the suborder Rhopalocera, namely butterflies. Butterflies play a very important role in supporting ecosystem balance and biodiversity. This study aims to determine the diversity and dominance indices of Rhopalocera suborder (butterflies) species in Langsa City Forest Park, Aceh. The study used observation methods during the rainy season. Methodology: Sampling was conducted using purposive sampling methods across three locations with varying environmental conditions and vegetation characteristics. Sampling was conducted using sweep net techniques with insect nets at the research sites. The quantitative descriptive analysis calculated was the diversity index and species dominance of butterflies. Findings: The Rhopalocera species found in Langsa City Forest Park consisted of 41 species belonging to 5 families The dominant family found is Nymphalidae, while the dominant species found is Leptosia nina from the Pieridae family. The overall Rhopalocera diversity index (H` = 3.10) falls into the high category, and all three research sites have moderate diversity indices. The highest diversity was found at Site I (H` = 2.86), which has a variety of plant vegetation and is near a lake. Meanwhile, the lowest diversity was found at location II, which is dominated by tree vegetation. Vegetation diversity creates habitats that support butterfly species development, while homogeneous vegetation structures can limit the availability of food sources and habitats, resulting in low species diversity. The species dominance index is included in low category. The diversity of Rhopalocera (butterflies) and their habitats is crucial to preserve in efforts to conserve the Langsa City Forest Park ecosystem. Contribution: this study are expected to provide useful information for the management and conservation of the area, as well as to raise public awareness about the importance of preserving biodiversity